2006
DOI: 10.1509/jmkg.70.4.56
|View full text |Cite
|
Sign up to set email alerts
|

It Just Feels Good: Customers' Affective Response to Touch and Its Influence on Persuasion

Abstract: Prior research has assumed that touch has a persuasive effect only if it provides attribute or structural information about a product. Under this view, the role of touch as a persuasive tool is limited. The main purpose of this research is to investigate the persuasive influence of touch as an affective tool in the absence of useful product-related information. The authors find that for people who are motivated to touch because it is fun or interesting, a communication that incorporates touch leads to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
223
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(236 citation statements)
references
References 29 publications
8
223
0
5
Order By: Relevance
“…The autotelic dimension is related to touch as an end in and of itself. As in other studies (Peck & Childers, 2006;Peck & Wiggins, 2006), the present research will consider only one NFT factor, in this case the instrumental factor. Instrumental NFT relates to an outcome-directed touch with a salient purchase goal.…”
Section: Impulse and Contemplative Behavior: Impulsiveness Vs Need Fmentioning
confidence: 99%
“…The autotelic dimension is related to touch as an end in and of itself. As in other studies (Peck & Childers, 2006;Peck & Wiggins, 2006), the present research will consider only one NFT factor, in this case the instrumental factor. Instrumental NFT relates to an outcome-directed touch with a salient purchase goal.…”
Section: Impulse and Contemplative Behavior: Impulsiveness Vs Need Fmentioning
confidence: 99%
“…Though, informational words on labeling are becoming more and more vital and influence choice in fast moving consumer goods. Customers can judge FMCG'S quality by seeing label if they were taking into account products more carefully (Peck & Wiggins, 2006). But, not all the essentials of packaging are same as with how Western customers react to packaging while doing shopping on impulse, so marketers in Asia have to adapt packaging in most effective ways.…”
Section: Discussionmentioning
confidence: 99%
“…Touching products has been shown to exert a positive impact on shopper attitudes and behaviour, as well as on purchase intentions (Citrin et al, 2003;Peck & Wiggins, 2006) and is associated with effective product placement in stores. Moreover, research has demonstrated that for some people, the effects of touch are stronger than for others (Peck & Childers, 2003a).…”
Section: Analyzing the Impact Of Sensory Marketing On Consumers 284mentioning
confidence: 99%
“…Moreover, research has demonstrated that for some people, the effects of touch are stronger than for others (Peck & Childers, 2003a). By using touch, a positive affective response might result in more positive attitudes toward a product (Peck & Wiggins, 2006). In this context, touch means gaining information about the product and its characteristics, such as form, hardness, texture, or weight.…”
Section: Analyzing the Impact Of Sensory Marketing On Consumers 284mentioning
confidence: 99%
See 1 more Smart Citation